IoT-Based Integrated Production and Quality Control System Design for Halal SMEs in Island Regions - Marasabessy, Sitnah Aisyah; Noor, Mohammad Azemi Mohd; Nusran, Muhammad; Ardian, Sony; Zurimi, Safarin; Nasrulyati, Tri Siwi; Henaulu, Agung K (JTI: Jurnal Teknik Industri, 2025)
The global halal economy continues to expand rapidly, creating a pressing demand for reliable and technology-driven quality management systems. However, small and medium-sized enterprises (SMEs) in Indonesia’s island regions face major constraints in ensuring consistent halal assurance due to limited resources, geographic isolation, and dependence on manual processes. This study proposes an IoT-based integrated production and quality control system tailored for halal SMEs in island settings. The framework integrates Total Quality Management (TQM), Halal Assurance System (HAS), and Industry 4.0 technologies. Using sensors to monitor temperature, humidity, and weight—connected to a cloud dashboard—the system enables real-time monitoring, traceability, and halal compliance. A prototype was implemented in fish processing SMEs in Maluku, Indonesia. Results show improvements in production efficiency (15%), product consistency (20%), and halal documentation readiness. The findings confirm that IoT integration strengthens halal assurance and offers a scalable digital transformation model for island-based halal industries worldwide.